Differential larval responses of two ecologically similar insects (Odonata) to temperature and resource variation - Chavez, M.Y. (Int. J. Odonatol., 2016)
How species respond to shifting environmental conditions is a central question in ecology, especially because ecosystems are experiencing rapidly changing climatic conditions. However, predicting the responses of species interactions and community composition to changing conditions is often difficult. We examined the effects of rearing temperature and resource level on larval survival of two ecologically similar dragonflies, Erythemis collocata and Pachydiplax longipennis. Within high and low (26 and 21°C) temperatures, we crossed species and resource level and reared larvae individually. We predicted that warmer temperatures would reduce survival and increase growth rate, that higher resource availability would increase survival and growth rate, and that the two species would respond similarly. We found that increased temperature reduced survival for both species. There was also an interaction between temperature and species: E. collocata had higher survival at the lower temperature, but lower survival at the higher temperature when compared to P. longipennis. Resource level did not affect survival. In general, P. longipennis grew more than E. collocata, with no effects of temperature or resource level. These results suggest that these species respond dissimilarly to changing thermal conditions, that increased food availability cannot always compensate for the negative effects of higher temperatures, and that climate change may affect interactions between these two sympatric, ecologically similar species, with potential consequences for community composition.